Adsorptive Removal of Pb(II) from Water Using Novel Synthesized Polyaniline Composites with Madhuca longifolia and Eugenia jambolana Leaf Powder - Kanwal, Farah; Rehman, Rabia; Anwar, Jamil; Rasul, Sadia (Asian Journal of Chemistry, 2014)
Novel polyaniline composites with plant leaf powder of Madhuca longifolia (Mahwa) and Eugenia jambolana (Jamun) (PANI/ML, PANI/JL) were synthesized for removal of Pb(II) from water. The optimum conditions of sorption were found on batch scale as followed: adsorbent dose 0.8 g in 50 mL solution of Pb(II), 90 min contact time, 4 pH and 30 °C temperature for PANI/ML and for PANI/JL: adsorbent dose 0.9 g in 50 mL solution of Pb(II), 90 min contact time, 2 pH and 50 °C temperature. Langmuir and Freundlich isotherm models were subjected to sorption data. Langmuir isotherm indicated monolayer chemisorptive removal of lead ions occurred more on homogeneously distributed binding sites on composites. The negative value of DG° confirmed the spontaneity and feasibility of adsorption process with maximum removal of Pb(II), whereas Freundlich model applicability indicated that binding sites are heterogeneously distributed in composites, facilitates physiosorptive removal of metal ions. KF values were: 0.857 and 0.500 for PANI/ML and PANI/JL respectively. The maximum adsorption capacities of PANI/ML composites is 3.891 mg/g, while in case of PANI/JL it was 5.917 mg/g. Results indicated that for Pb(II) removal, PANI/JL is better adsorbent and shows more adsorption as compared to PANI/ML.